If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3 = 3x + 12 Reorder the terms: -3 + 2x = 3x + 12 Reorder the terms: -3 + 2x = 12 + 3x Solving -3 + 2x = 12 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -3 + 2x + -3x = 12 + 3x + -3x Combine like terms: 2x + -3x = -1x -3 + -1x = 12 + 3x + -3x Combine like terms: 3x + -3x = 0 -3 + -1x = 12 + 0 -3 + -1x = 12 Add '3' to each side of the equation. -3 + 3 + -1x = 12 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 12 + 3 -1x = 12 + 3 Combine like terms: 12 + 3 = 15 -1x = 15 Divide each side by '-1'. x = -15 Simplifying x = -15
| x+0.02=870 | | 2x+16=42 | | -17/4(-20)+60 | | 2x+17=39 | | -5(2b+1)+(11b-7)=0 | | -1=5+n | | 72=3x(x+2) | | 1.3q-3.8-5.6q=-5.3q-4.3 | | 130=10x+7y | | -14=-7m | | 4+9y-3=7y+43-4y | | 729p^2-36= | | .49x^2+12x=20 | | 15+10x+x^2=0 | | -21/4(-10)+80 | | 2h+1=-17 | | -10=10a | | 18x-12=22x+8 | | 3k=-12 | | 8-5x=-22 | | 8-5x=-22 | | 12.5*n=100 | | 4x^3-9x^2-x-6=0 | | -21/4(-10) | | 31=-7+x | | -21/4(10) | | 2(x+22)=5+3(x-2)-4x | | -3x8+4/(-2) | | r-45=-45 | | 9g+11=-2 | | 4xy^2+44x^2y^2-28xy^2=0 | | 3/4w=-16/27 |